Handedness as a neurodevelopmental marker in schizophrenia: Results from the FACE-SZ cohort. (9th August 2022) - Mallet, Jasmina; Godin, Ophélia; Le Strat, Yann; Mazer, Nicolas; Berna, Fabrice; Boyer, Laurent; Capdevielle, Delphine; Clauss, Julie; Chéreau, Isabelle; D'Amato, Thierry; Dubreucq, Julien; Leigner, Sylvain; et al.
Abstract: Objectives: High rates of non-right-handedness (NRH) including mixed-handedness have been reported in neurodevelopmental disorders. In schizophrenia (SZ), atypical handedness has been inconsistently related to impaired features. We aimed to determine whether SZ subjects with NRH and mixed-handedness had poorer clinical and cognitive outcomes compared to their counterparts. Methods: 667 participants were tested with a battery of neuropsychological tests, and assessed for laterality using the Edinburg Handedness Inventory. Clinical symptomatology was assessed. Learning disorders and obstetrical complications were recorded. Biological parameters were explored. Results: The prevalence of NRH and mixed-handedness was high (respectively, 42.4% and 34.1%). In the multivariable analyses, NRH was associated with cannabis use disorder ( p  = 0.045). Mixed-handedness was associated with positive symptoms ( p  = 0.041), current depressive disorder ( p  = 0.005)), current cannabis use ( p  = 0.024) and less akathisia ( p  = 0.019). A history of learning disorder was associated with NRH. No association was found with cognition, trauma history, obstetrical complications, psychotic symptoms, peripheral inflammation. Conclusions: Non-right and mixed-handedness are very high in patients with SZ, possibly reflecting a neurodevelopmental origin. NRH is associated with learning disorders and cannabis use. Mixed-handedness is associated with positive symptoms, current depressive disorder, cannabis use and less akathisia. However, this study did not confirm greater cognitive impairment in these patients.